Nitrogen-containing steel die casting covering slag and preparation process thereof
By introducing AlN, Si, and Al elements into the protective slag, and utilizing the exothermic reaction of aluminum ash and the glassy slag film, the problem of nitrogen precipitation during the casting of nitrogen-containing molten steel was solved. This improved the inhibition of porosity and cracks in the ingot, enhanced the quality of the ingot, and facilitated the resource utilization of aluminum ash.
Patent Information
- Application Number
- CN202511530099.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-06
AI Technical Summary
In the existing technology, nitrogen is unstable during the casting of nitrogen-containing molten steel, which can easily lead to quality problems such as subcutaneous porosity and cracks in the billet. In particular, nitrogen precipitation tends to be obvious in the ingot casting process, and conventional protective slag cannot effectively control porosity and cracks in large ingots.
A nitrogen-containing mold casting protective slag is used, which is composed of iron oxide powder, wollastonite, calcined slag, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride and bauxite. By introducing a specific proportion of AlN into the protective slag, the AlN in the aluminum ash decomposes at about 1200℃ to release free nitrogen, thereby increasing the nitrogen partial pressure on the slag side, inhibiting nitrogen precipitation in the steel, and alleviating the temperature difference through the exothermic reaction of Si and Al elements to form a glassy slag film, which inhibits nitrogen escape.
It significantly reduces the incidence of subcutaneous porosity and cracks in nitrogen-containing steel mold castings, improves ingot quality, realizes high-value resource utilization of aluminum ash, takes into account the surface and internal purity of large ingots, and improves ingot yield.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of protective slag technology, specifically relating to a nitrogen-containing steel mold casting protective slag and its preparation process. Background Technology
[0002] Research based on the development of metallurgical technology and the actual needs of industrial manufacturing has revealed that nitrogen plays an increasingly important role in the alloying of certain steel grades, such as valve steel, generator rotor retaining ring steel, some austenitic stainless steels, tool steels, die steels, and some high-strength and high-toughness structural steels. Nitrogen can significantly enhance the formation and stabilization of austenite in molten steel. By adding a certain amount of nitrogen to steel, the strength, plasticity, and corrosion resistance of the steel can be significantly improved.
[0003] Currently, the main methods to increase the nitrogen content in molten steel are to add solid nitrogen-containing alloys to the molten steel or to promote the formation of a eutectic mixture between nitrogen and iron by blowing argon gas into the molten steel, thereby achieving the goal of increasing nitrogen content in the molten steel.
[0004] Existing research indicates that nitrogen mainly dissolves in molten steel as free nitrogen atoms, and its solubility is related to many factors, such as: (1) The effect of changes in ambient temperature. The higher the temperature, the greater the partial pressure of nitrogen, and the higher the solubility of nitrogen in molten steel.
[0005] (2) The influence of alloy composition of molten steel. For example, elements such as chromium, manganese, and vanadium have a strong chemical affinity for nitrogen, which can cause a sharp increase in the solubility of nitrogen in steel.
[0006] (3) The influence of active substances in molten steel. For example, elements such as oxygen and sulfur will occupy some of the surface sites for adsorbing nitrogen in molten steel, thus hindering the dissolution of nitrogen in molten steel.
[0007] In actual production, the thermal and chemical environments of the molten steel corresponding to the aforementioned influencing factors are all variables, which can cause the dissolved nitrogen in the molten steel to be in an unstable state. Especially during the casting and solidification process of molten steel, due to the significant drop in temperature, nitrogen in the molten steel will precipitate in the form of bubbles or penetrate into low-nitrogen areas (near the protective slag), which can easily cause quality problems such as porosity under the surface of the billet (ingot) and stress concentration leading to cracks. In view of this, this invention is proposed. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is to provide a nitrogen-containing steel mold casting protective slag that utilizes aluminum ash to solve the problem of nitrogen precipitation during the solidification process of nitrogen-containing steel mold casting ingots, thereby significantly reducing the incidence of subcutaneous porosity and cracks in nitrogen-containing steel mold casting ingots.
[0009] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a nitrogen-containing steel mold casting protective slag, made of iron oxide powder, wollastonite, calcite, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride, and bauxite, wherein the weight parts of the iron oxide powder are 3-7 parts, the weight parts of the wollastonite are 15-30 parts, the weight parts of the calcite are 10-40 parts, the weight parts of the aluminum ash are 8-18 parts, the weight parts of the ferrosilicon powder are 2-7 parts, the weight parts of the quartz are 20-30 parts, the weight parts of the lithium carbonate are 1-3 parts, the weight parts of the sodium fluoride are 1-5 parts, and the weight parts of the bauxite are 10-25 parts.
[0010] This invention addresses quality problems such as porosity and cracks in nitrogen-containing steel ingots caused by nitrogen precipitation. It introduces aluminum ash containing a specific proportion of aluminum nitride (AlN) into the protective slag formulation, combined with specific fluxes and other raw materials. This allows the protective slag to decompose and release a certain amount of free nitrogen at around 1200℃, increasing the nitrogen partial pressure on the slag side and effectively inhibiting nitrogen precipitation from the steel. This prevents subsurface porosity and cracks in nitrogen-containing steel ingots, significantly improving the quality of nitrogen-containing steel ingots. Specifically, this invention selects iron oxide powder, wollastonite, calcined alumina, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride, and bauxite to form a mixture of CaO, SiO2, Fe2O3, Al2O3, NaO2, and F... - The protective slag with Li2CO3, Si, Al and AlN as effective components is applied to nitrogen-containing steel mold casting. Practice has proved that the protective slag product of this invention can be adapted to various specifications of nitrogen-containing steel mold casting, and can play a significant role in improving the porosity and crack defects of nitrogen-containing steel.
[0011] Preferably, the iron oxide powder contains ≥85% Fe2O3 by weight and has a particle size of -100 mesh.
[0012] Preferably, the wollastonite contains ≥51% SiO2 by weight, ≥39% CaO by weight, and has a particle size of -100 mesh.
[0013] Preferably, the fused gemstone contains ≥51% SiO2 by weight, ≥42% Al2O3 by weight, and has a particle size of -100 mesh.
[0014] Preferably, the aluminum ash contains ≥45% by weight of Al2O3, ≥5% by weight of Al, ≥8% by weight of AlN, ≤10% by weight of SiO2, and has a particle size of -100 mesh.
[0015] Preferably, the ferrosilicon powder contains ≥75% Si by weight and has a particle size of -100 mesh.
[0016] Preferably, the quartz contains ≥98% SiO2 by weight and has a particle size of -100 mesh.
[0017] Preferably, the lithium carbonate contains ≥98% Li2CO3 by weight and has a particle size of -100 mesh.
[0018] Preferably, the sodium fluoride contains ≥98% NaF by weight and has a particle size of -100 mesh.
[0019] Preferably, the bauxite contains ≥50% Al2O3 by weight, ≥13% Fe2O3 by weight, ≤20% SiO2 by weight, and has a particle size of -100 mesh.
[0020] Therefore, each raw material, while meeting the above-mentioned chemical composition requirements, can better achieve the function of protective slag.
[0021] Preferably, the nitrogen-containing steel casting protective slag has the following effective component mass percentages: CaO: 5.8-12.0%, SiO2: 37.0-56.0%, Fe2O3: 3.8-9.2%, Al2O3: 14.5-27.0%, NaF: 0.98-4.90%, Li2CO3: 0.98-2.95%, Si: 1.5-5.3%, Al: 0.4-1.0%, AlN: 0.6-1.6%, with the balance being unavoidable impurities.
[0022] Preferably, the protective slag has a binary basicity of <0.9, a melting point of 1050-1100℃, and a viscosity of 0.35-0.85 Pa·s at 1350℃.
[0023] The present invention also provides the above-mentioned nitrogen-containing steel mold casting protective slag, which is prepared efficiently to achieve the full effect of the protective slag.
[0024] The preparation method of the above-mentioned nitrogen-containing steel ingot casting protective slag includes the following steps: (1) Provide iron oxide powder, wollastonite, coke, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride and bauxite, crush and screen each raw material, control the moisture content to be less than 1%, and process it into fine powder; (2) Sample each raw material and test its chemical composition; (3) After the chemical composition is determined, the proportion of each raw material is designed; (4) Weigh each raw material precisely according to the proportions and add it to the disc mixer for mixing; (5) Grind the product using a ball mill until the particle size is uniform, take a sample for inspection, and ensure that the moisture content of the finished product is less than 0.1%. Finally, package and store the product.
[0025] The fine powder has a particle size of -100 mesh, and 100 mesh corresponds to a fine powder particle size of approximately 0.15 mm, meaning the fine powder particle size is ≤0.15 mm.
[0026] A method for using a nitrogen-containing steel mold casting protective slag includes: adding the protective slag to the bottom of the mold before casting the steel, with an addition amount of 0.5-1.5 kg / ton of steel.
[0027] In steel production, there are two main technical routes for solidification of molten steel: continuous casting and ingot casting.
[0028] Continuous casting, also known as continuous steel casting, is a core process in modern steel production. It involves continuously injecting high-temperature molten steel into a water-cooled crystallizer through a tundish, rapidly cooling it to form solid steel billets (square billets, slabs, round billets, etc.), and then continuously pulling them out through a straightening device to finally cut them into fixed lengths. The advantages of continuous casting are: (1) high production efficiency, low energy consumption, and metal yield of over 95%; (2) continuous process, easy to automate. However, rapid cooling and stress during casting make the billets prone to cracking and central segregation, and the short time for inclusions to float limits cleanliness.
[0029] Ingot casting is a process in which molten steel is placed in a steel ingot mold and solidifies naturally. Its characteristics are: (1) long solidification time, inclusions float to the surface, and the cleanliness is better than continuous casting; (2) slow cooling and single stress, and the crack rate of ingots of the same specification is lower than that of continuous casting; (3) suitable for manufacturing large or complex-shaped forgings and thick special steels. Therefore, nitrogen-containing steels used in high-end fields such as energy, military industry, and molds generally adopt the ingot casting process. At the same time, the disadvantages of the ingot casting process are: (1) slow production pace and low metal yield; (2) easy to produce defects such as shrinkage cavities, porosity, and segregation, which need to be improved by subsequent forging or rolling. Especially for large ingots with a diameter of φ450mm or more, the solidification time can reach several hours, and the temperature difference between the center and the surface is large, which easily leads to nitrogen enrichment and precipitation on the surface, forming obvious defects such as subcutaneous pores and cracks.
[0030] To alleviate the above-mentioned defects in the die casting process, the industry has developed a special die casting protective slag for nitrogen-containing steel. For example, patent document CN109365789A discloses a special die casting protective slag for nitrogen-containing steel with the following effective components: CaO: 12-27%, NaO2: 5-10%, Li2O: 1-3%, MgO: 2-6%, Al2O3: 8-15%, SiO2: 28-45%, Fe2O3: 2-4%, CaF2: 4-8%, C: 0.6-1.2%, BN: 1-4%. This formula uses BN to replace part of the carbon as the skeleton particles, which can improve lubrication, reduce cracks, porosity and inclusions, but still has the following bottlenecks: (1) BN has a high melting point and a decomposition temperature much higher than the billet smelting temperature. It is difficult to release free nitrogen in time during the solidification stage of the molten steel, and it cannot effectively balance the low nitrogen partial pressure on the slag side. The tendency of nitrogen precipitation is still obvious; (2) There is a lack of targeted control methods for porosity or crack problems caused by long-term, high-gradient temperature fields in large ingots.
[0031] Moreover, with the continuous progress and development of metallurgical research, the mass percentage of nitrogen in some nitrogen-containing steels has gradually increased, from 0.10-0.20% to 0.3-0.5%, and the nitrogen precipitation phenomenon has become more obvious.
[0032] In addition, my country's electrolytic aluminum industry generates millions of tons of aluminum ash (containing Al, Al2O3, AlN, etc.) annually. AlN can release ammonia when it comes into contact with moisture and is classified as HW48 in the "National Hazardous Waste List (2021 Edition)". Conventional landfilling or stockpiling occupies land and poses high environmental risks, while harmless treatment is extremely costly.
[0033] In summary, there is an urgent need to develop a protective slag solution that can control nitrogen precipitation, realize the high-value resource utilization of aluminum ash, and take into account both the surface quality and internal purity of large nitrogen-containing steel ingots.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The protective slag of this invention contains appropriate amounts of Si and Al elements, eliminating the need for any additional operations or environmental upgrades during the casting preparation stage. At the beginning of casting, these elements undergo exothermic reduction reactions with their own oxides or active oxygen at the interface with the molten steel within the slag layer, instantly releasing heat to offset the initial temperature difference between the molten steel and the mold, thus achieving slow cooling and solidification of the ingot. This creates thermodynamic conditions for controlled and limited nitrogen precipitation, suppressing nitrogen-induced defects in the later stages. At the same time, the protective slag extends the effective time for inclusions in the steel to float and be captured, significantly improving the purity of the steel. When combined with conventional ingot riser heating agents, the riser feeding is more thorough, the surface is smoother, the crack incidence rate decreases simultaneously, and the ingot yield is further improved.
[0035] (2) The binary basicity CaO / SiO2 of the mold casting protective slag of the present invention is less than 0.9, which belongs to the acidic slag system. The slag as a whole maintains an oxidizing atmosphere. A certain amount of high-grade iron oxide powder (Fe2O3≥85%) is added to further enhance the oxidizing property. As a result, active oxygen preferentially occupies the adsorption sites of nitrogen at the steel-slag interface, significantly inhibiting the nitrogen escape rate and delaying the process of nitrogen precipitation from the molten steel to the gas phase.
[0036] (3) The protective slag of the present invention utilizes AlN in aluminum ash, which combines with flux in the slag to form an easily decomposable phase. It can decompose and release free nitrogen at approximately 1200℃, thereby increasing the nitrogen partial pressure on the slag side. In this way, on the one hand, it inhibits the precipitation of nitrogen in the molten steel, and on the other hand, the free nitrogen can be reabsorbed by the molten steel, thus achieving the dual functions of controlled precipitation and nitrogen replenishment.
[0037] (4) The protective slag of the present invention is formed by combining appropriate amounts of Li2CO3, NaF and Fe2O3 to form a flux system, which significantly promotes the high-temperature glassization degree of the protective slag, can efficiently capture and dissolve Al2O3 inclusions generated by Al deoxidation in nitrogen-containing steel liquid, and reduce the number of inclusions on the surface of the billet; significantly optimizes the film coating state of the protective slag on the surface of the billet, the glassy slag film has high thermal stability, inhibits uncontrollable crystallization caused by temperature fluctuations after adsorption of inclusions, and ensures that the slag film is uniformly and continuously distributed between the surface of the billet and the inner wall of the mold; thereby synchronizing heat transfer and solidification, reducing local stress concentration, and significantly reducing the incidence of subcutaneous cracks.
[0038] (5) This invention uses aluminum ash, a waste product of electrolytic aluminum, as a functional component to improve the efficiency of mold casting protective slag. In terms of smelting effect, it utilizes the controllable decomposition of AlN in aluminum ash to adjust the nitrogen partial pressure at the slag-steel interface, thereby solving the problem of nitrogen precipitation during the solidification process of nitrogen-containing steel mold casting ingots and significantly reducing the incidence of subcutaneous porosity and cracks. In terms of environmental protection effect, it utilizes the high value and resource utilization of bulk hazardous waste aluminum ash, which has significant economic and environmental benefits. Detailed Implementation
[0039] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details.
[0040] Unless otherwise specified, all raw materials are derived from commercially available products and do not contain any unspecified components other than unavoidable impurities.
[0041] In the following examples, each raw material meets the following requirements: Iron oxide powder, containing ≥85% Fe2O3 by weight.
[0042] Wollastonite, containing ≥51% SiO2 by weight and ≥39% CaO by weight.
[0043] Fiber ore, containing ≥51% SiO2 by weight and ≥42% Al2O3 by weight.
[0044] Aluminum ash, containing ≥45% by weight of Al2O3, ≥5% by weight of Al, ≥8% by weight of AlN, and ≤10% by weight of SiO2.
[0045] Ferrosilicon powder, containing ≥75% Si by weight.
[0046] Quartz, containing ≥98% SiO2 by weight.
[0047] Lithium carbonate, containing ≥98% by weight of Li2CO3.
[0048] Sodium fluoride, containing ≥98% NaF by weight.
[0049] Iron bauxite, containing ≥50% by weight of Al2O3, ≥13% by weight of Fe2O3, and ≤20% by weight of SiO2.
[0050] All the above raw materials have passed through a 100-mesh sieve.
[0051] A nitrogen-containing protective slag for steel ingot casting is made of iron oxide powder, wollastonite, calcined alumina, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride, and bauxite. The weight percentages of iron oxide powder are 3-7 parts, wollastonite is 15-30 parts, calcined alumina is 10-40 parts, aluminum ash is 8-18 parts, ferrosilicon powder is 2-7 parts, quartz is 20-30 parts, lithium carbonate is 1-3 parts, sodium fluoride is 1-5 parts, and bauxite is 10-25 parts.
[0052] The effective components of the nitrogen-containing steel mold casting protective slag are as follows (mass percentage): CaO: 5.8-12.0%, SiO2: 37.0-56.0%, Fe2O3: 3.8-9.2%, Al2O3: 14.5-27.0%, NaF: 0.98-4.90%, Li2CO3: 0.98-2.95%, Si: 1.5-5.3%, Al: 0.4-1.0%, AlN: 0.6-1.6%, with the balance being unavoidable impurities.
[0053] The binary basicity of the nitrogen-containing steel mold casting protective slag is <0.9, the melting point is 1050~1100℃, and the viscosity at 1350℃ is 0.35~0.85Pa·s.
[0054] The following is an implementation example.
[0055] The raw materials and weight proportions of the nitrogen-containing steel mold casting protective slag in Examples 1-10 are shown in Table 1.
[0056] Table 1. Raw materials and weight proportions of nitrogen-containing steel ingot casting protective slag in Examples 1-10 The effective components and their mass percentages of the nitrogen-containing steel mold casting protective slag in Examples 1-10 are shown in Table 2.
[0057] Table 2. Effective components and their mass percentages of nitrogen-containing protective slag for steel ingot casting. The physicochemical properties of the protective slags in Examples 1-10 meet the following requirements: binary basicity < 0.9, melting point 1050–1100℃, and viscosity 0.35–0.85 Pa·s at 1350℃. Specific test results are shown in Table 3.
[0058] Table 3 Physicochemical properties of protective slag in Examples 1-10 Table 3 shows that the protective slags prepared in Examples 1-10 all meet the above-mentioned physicochemical properties.
[0059] The protective slags in Examples 1-10 were prepared by the method provided in Example 11 below.
[0060] Example 11: A method for preparing a nitrogen-containing steel mold casting protective slag, comprising the following steps: (1) Provide iron oxide powder, wollastonite, coke, aluminum ash, ferrosilicon powder, quartz, lithium carbonate, sodium fluoride and bauxite. Crush and screen each raw material, control the moisture content to be less than 1%, and process it into fine powder and pass it through a 100-mesh sieve. (2) Sample each raw material and test its chemical composition; (3) After the chemical composition is determined, the proportion of each raw material is designed; (4) Weigh each raw material precisely according to its proportion and add it to the disc mixer for mixing. (5) Grind the product using a ball mill until the particle size is uniform, take a sample for inspection, and ensure that the moisture content of the finished product is less than 0.1%. Finally, package and store the product.
[0061] The method for using the above-mentioned nitrogen-containing steel mold casting protective slag includes: before casting the steel, adding any of the protective slags from Examples 1-10 to the bottom of the mold, with an addition amount of 0.5-1.5 kg / ton of steel. Any value within the above range can be selected according to actual needs.
[0062] The following are comparative examples.
[0063] Comparative Example 1: A nitrogen-containing mold casting protective slag, which differs from Example 1 only in that BN is used instead of aluminum ash.
[0064] Comparative Example 2: A nitrogen-containing steel mold casting protective slag, which differs from Example 1 only in that ferrosilicon powder is omitted.
[0065] Comparative Example 3: A nitrogen-containing steel mold casting protective slag, which differs from Example 1 only in that aluminum ash is omitted.
[0066] Comparative Example 4: A nitrogen-containing protective slag for steel ingot casting, which differs from Example 1 only in that the aluminum ash is 20 parts by weight.
[0067] Comparative Example 5: A nitrogen-containing steel mold casting protective slag, which differs from Example 1 only in that the amount of ferrosilicon powder is 10 parts by weight.
[0068] Comparative Example 6: A nitrogen-containing steel mold casting protective slag, which differs from Example 1 only in that it contains 1 part by weight of iron oxide powder, 5 parts by weight of lithium carbonate, and 6 parts by weight of sodium fluoride.
[0069] Comparative Example 7: A nitrogen-containing steel mold casting protective slag, using Example 1 described in patent document CN109365789A.
[0070] Next, the content of the evaluation test will be explained.
[0071] (1) Evaluation method: (1.1) The protective slag prepared in Examples 1-6 and Comparative Examples 1-6 was used for nitrogen-containing steel ingot casting. The diameter of the ingot was φ260-450mm. Before casting the steel, the protective slag was added to the bottom of the mold at a rate of 0.7Kg / ton of steel.
[0072] (1.2) The protective slag prepared in Examples 1-3 and Comparative Example 7 was used for nitrogen-containing steel ingot casting. The diameter of the ingot was φ500-850mm. Before casting the steel, the protective slag was added to the bottom of the mold at a rate of 1.2Kg / ton of steel.
[0073] The ingots obtained above were sampled and analyzed from the head, middle and tail sections respectively.
[0074] (2) Evaluation indicators: (2.1) Porosity: The lower 3mm longitudinal section of the ingot billet was treated by cold acid etching method in GB / T226-2015, the porosity was detected, and the porosity was calculated, where: porosity = sum of the areas of individual pores / total area of the observation field × 100%; (2.2) Crack rate: The billet is treated by cold acid corrosion method in GB / T226-2015. Cracks with a depth of 1-3 mm and a length of 2-7 mm are detected in the billet. The crack rate is calculated, where: Crack rate = Sum of projected crack areas / Total area of observation field × 100%; (2.3) Nitrogen deviation rate: The nitrogen content of steel at the center of the ingot and 5mm below the billet is tested, and the relative deviation rate is calculated. Relative deviation rate = actual nitrogen content - theoretical nitrogen content / theoretical nitrogen content × 100%.
[0075] (2.4) Inclusion content: The inclusion content in the billet sample was detected and counted using a scanning electron microscope and a large-area energy dispersive spectrometer.
[0076] (3) Evaluation results: The average value of the three sampling tests was taken, and the results are shown in Tables 4-6.
[0077] Table 4 Evaluation results of Examples 1-6 (ingot diameter of mold casting is φ260-450mm) Table 5 Evaluation results of comparative examples 1-6 (ingot diameter of mold casting is φ260-450mm) Table 6 Evaluation results of Examples 1-3 and Comparative Example 7 (ingot diameter φ500-850mm) As shown in Table 4, the protective slag of this invention produces nitrogen-containing steel ingots with a diameter of φ260-450mm with a porosity of <1.0%, a crack rate of <1.0%, a nitrogen deviation rate of <2.0%, and an inclusion content level of ≤10%. 3 The effect of using it is remarkable.
[0078] As shown in Table 5: (1) After BN completely replaced aluminum ash in Comparative Example 1, the various test indicators of the billet deteriorated significantly, indicating that aluminum ash (containing Al and AlN) cannot be simply replaced by BN, and the effect of the replacement exceeded the conventional expectations. (2) Comparative Examples 2-5 showed varying degrees of decrease in indicators by reducing or adjusting the amounts of ferrosilicon powder (for Si) and aluminum ash (for Al and AlN), indicating that Si, Al, and AlN need to be properly matched within the protective slag. When the amount is insufficient, the heat release is insufficient, the slow cooling effect of the billet shell is lost, and the nitrogen precipitation inhibition fails; when the amount is excessive, the oxidation-reduction reaction is too intense, the slag system is unbalanced, and the function also deteriorates unexpectedly.
[0079] (3) When the ratio of iron oxide powder, lithium carbonate and sodium fluoride in Comparative Example 6 deviated from the scope of the present invention, the evaluation index decreased significantly, indicating that the flux system has a supporting effect on the overall performance of the protective slag.
[0080] Therefore, aluminum ash, ferrosilicon powder and flux form a synergistic system in the protective slag of this invention. The absence or imbalance of any component will destroy the synergistic mechanism of exothermic, slow cooling and nitrogen precipitation inhibition, resulting in the deterioration of the quality of nitrogen-containing steel casting.
[0081] As shown in Table 6, the protective slag of this invention produces nitrogen-containing steel ingots with a diameter of φ500-850mm with a porosity of <2.0%, a crack rate of <1.5%, a nitrogen deviation rate of <4.0%, and an inclusion content level of ≤10%. 5 Comparative Example 7 adopts Example 1 described in patent document CN109365789A. All three indicators are significantly higher than the above limits, indicating that the protective slag of the present invention effectively suppresses the porosity and crack defects caused by large ingots due to large temperature gradients and long solidification times through the synergistic mechanism of exothermic, slow cooling and nitrogen precipitation inhibition, thus making up for the shortcomings of the prior art.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A nitrogen-containing steel mold casting protective mold characterized by: It is made of iron oxide powder, wollastonite, calcined bauxite, aluminum ash, silicon iron powder, quartz, lithium carbonate, sodium fluoride, iron ore, the weight fraction of the iron oxide powder is 3-7 parts, the weight fraction of the wollastonite is 15-30 parts, the weight fraction of the calcined bauxite is 10-40 parts, the weight fraction of the aluminum ash is 8-18 parts, the weight fraction of the silicon iron powder is 2-7 parts, the weight fraction of the quartz is 20-30 parts, the weight fraction of the lithium carbonate is 1-3 parts, the weight fraction of the sodium fluoride is 1-5 parts, and the weight fraction of the iron ore is 10-25 parts.
2. A nitrogen-containing steel mold casting protective mold according to claim 1, characterized by: The iron oxide powder contains Fe2O3≥85% by weight and has a particle size of-100 mesh.
3. A nitrogen-containing steel mold casting protective mold according to claim 2, characterized by: The aluminum ash contains Al2O3≥45% by weight, Al≥5% by weight, AlN≥8% by weight, SiO2≤10% by weight, and has a particle size of-100 mesh.
4. A nitrogen-containing steel mold casting protective mold according to claim 3, characterized by: The silicon iron powder contains Si≥75% by weight and has a particle size of-100 mesh.
5. A nitrogen-containing steel die casting protective mold flux as claimed in claim 4, characterized by: The iron ore contains Al2O3≥50% by weight, Fe2O3≥13% by weight, and SiO2≤20% by weight, and has a particle size of-100 mesh.
6. A nitrogen-containing steel die casting protective mold flux as claimed in claim 5, characterized by: The effective components have a mass percentage of CaO: 5.8-12.0%, SiO2: 37.0-56.0%, Fe2O3: 3.8-9.2%, Al2O3: 14.5-27.0%, NaF: 0.98-4.90%, Li2CO3: 0.98-2.95%, Si: 1.5-5.3%, Al: 0.4-1.0%, AlN: 0.6-1.6%, and the rest is inevitable impurities.
7. A nitrogen-containing steel die casting protective mold flux as claimed in claim 6, characterized by: Its binary alkalinity is <0.
9.
8. A nitrogen-containing steel die casting protective mold flux according to claim 7, characterized by: The melting point is 1050-1100℃.
9. A nitrogen-containing steel die casting protective mold flux according to claim 8, characterized by: The viscosity at 1350℃ is 0.35-0.85 Pa·s.
10. A method of producing a nitrogen-containing steel mould casting protective moulding sand according to any one of claims 1 to 9, characterised in that: It includes the following steps: (1) providing iron oxide powder, wollastonite, calcined bauxite, aluminum ash, silicon iron powder, quartz, lithium carbonate, sodium fluoride, and iron ore, crushing and sieving each raw material, controlling the water content to be less than 1%, and processing into fine powder; (2) sampling each raw material and detecting the chemical composition; (3) after determining the chemical composition, proportioning each raw material; (4) accurately weighing according to the proportioning of each raw material, mixing and stirring in a disc stirrer; (5) grinding to uniform particle size using a ball mill to obtain the finished product, sampling and testing to ensure that the moisture content in the finished product is <0.1%, and finally packaging and warehousing.
Citation Information
Patent Citations
Nitrogen-containing steel mold casting powder
CN109365789A